Fluorinated Graphene Contacts and Passivation Layer for MoS2 Field Effect Transistors (Adv. Electron. Mater. 10/2022). (10th October 2022) - Ryu, Huije; Kim, Dong‐Hyun; Kwon, Junyoung; Park, Sang Kyu; Lee, Wanggon; Seo, Hyungtak; Watanabe, Kenji; Taniguchi, Takashi; Kim, SunPhil; van der Zande, Arend M.; Son, Jangyup; Lee, Gwan‐Hyoung
Abstract : MoS2 Field Effect Transistors In article number 2101370, Jangyup Son, Gwan‐Hyoung Lee, and co‐workers suggest a facile one‐step technique utilizing fluorinated graphene as the passivation and contact buffer layer to MoS2, leading to the formation of Ohmic contacts and high carrier mobility of up to 64 cm 2 V −1 s −1 . The work provides a strategy for high‐performance 2D semiconductor electronics.